Moderasi Beragama: Bentuk Habituasi dan Aktualisasinya serta Kendala dan Hambatannya dalam Pendidikan Agama Hindu di Sekolah Menengah Atas - I Wayan Agus Gunada; I Made Ardika Yasa; Ida Bagus Alit Arta Wiguna; Ida Bagus Kade Yoga Pramana; I Wayan Rudiarta; Gusti Putu Budiarsana; I Made Aditya Mudita (Kamaya: Jurnal Ilmu Agama, 2023)
This research aims to describe and examine the obstacles and obstacles to the life process of religious moderation in Hindu learning in high school education in Mataram City. The city of Mataram consists of a reasonably plural community life, including the lives of people who adhere to diverse religions, with most Muslims. Tolerance among religious believers is capital in building hope for the development of a harmonious life in the community. Hindu learning in high schools becomes a habituation in building the foundation of moderate religious life. However, its integration in learning has obstacles that will undoubtedly hinder the acceleration of the development of religious moderation among students as a national resource. This study uses qualitative research with a case study approach with data collection techniques, namely observation, interviews and document studies. Based on the results of the study and analysis of the data, there are obstacles and obstacles in the form of not optimal learning in the learning process of religious moderation in Hindu religious education. This is because the material on religious moderation has not been directly written. However, in essence, it is contained in materials such as yajna values, catur asrama, upaveda, catur Warna, Vedic as a source of Hindu law and dasa Yama and nyama brata as a teaching of self-control in Hinduism. It is hoped that through this study, Hindu students at the high school level can understand and implement religious moderation learning in building a harmonious and tolerant life when entering society. This study can also be a reference library for relevant research in the future.